Design and performance evaluation of an innovative liquid-cooled battery thermal management system with hexagonal six-flow path channels: Energy and exergy analyses - Abanoz, Beyzanur Yavuz; Bayramoglu, Kubilay; Polat, Fikret; Saridemir, Suat; Agbulut, Umit (PERGAMON-ELSEVIER SCIENCE LTD, 2026)
The share of electric vehicles (EVs) in the transportation sector is accelerating day by day, as they have the potential to play a major role in controlling emissions that pose a major threat to life, preserving the ecological balance, and improving human prosperity. In order for lithium-ion batteries (LIBs), which are the power source of EVs, to provide the range and service life values they promise under safe driving conditions, battery thermal management systems (BTMSs) must be incorporated into the vehicle in an appropriate and effective manner. In this paper, the focus is on the thermal performance enhancement of liquid cooling based BTMSs and optimum cooling system scenarios. The innovative design of the battery pack was created by combining 28 LIBs, six-flow path cooling channels, and heat-dissipating aluminum sheets. In the study carried out at 5C discharge conditions, the effects of the cooling channel contact surface, the inlet velocity, and different flow directions (namely Case-1 to 5) on the thermal management performance were discussed. Additionally, energy and exergy analyses were conducted for all operating conditions and system performances and thermodynamic evaluations were compared. The results revealed that the cooling channel height, inlet velocity, and multiple flow orientations resulted in a noticeable effect on the system cooling performance. The best cooling performance and temperature uniformity were achieved in the cooling channel with the height of 13 mm. Increasing the inlet velocity from 0.05 m/s to 0.10 m/s reduced the maximum temperature by up to approximately 4.87 degrees C. Additionally, the battery exergy ranges from approximately 2.29 kW to 4.95 kW, with the lowest value observed at the 13 mm channel height and the highest value at the 8 mm channel height.
Keywords: Battery thermal management system; Cooling; Exergy analyses; Temperature uniformity; Thermodynamics; Mechanics